Tumbuh Bersama Saudara Kandung Autism Spectrum Disorder (ASD) : Pemaknaan Sibling Relationship Pada Remaja - Annisa, Fitria Eka; Octavia, Indah Andika; Adiyanti, Maria Goretti (Al-Qalb : Jurnal Psikologi Islam, 2022)
Abstract: Sibling relationships will be unique case when it terms of the perspective of adolescents who have siblings with Autism Spectrum Disorder (ASD). The inability of Autism Spectrum Disorder (ASD) children in building social interaction and communication with the surrounding environment, can affect social development in adolescents. This study aims to explore the meaning of sibling relationships in adolescents who have siblings with Autism Spectrum Disorder (ASD) and the dynamics of the emergence of these meanings. This study used qualitative method with a phenomenological approach. The main participants in this study amounted with three people. Data collection uses in-depth interviewing techniques and documentation. The results of this study indicate that adolescents who have siblings with Autism Spectrum Disorder (ASD) interpret sibling relationships as a gift from God, which aims to change their thinking, emotional conditions and behavior to become more mature. In addition, the quality of sibling relationships that are owned can be influenced by life values such as religious values and moral values related to harmony in family relationships.